Effect of neodymium ions on density and elastic properties of zinc tellurite glass systems - A. A., Abdulbaset; Mohamed Kamari, Halimah; Abd. Azis, Muhammad Norazlan (Scientific.Net, 2017)
The aim of this work is to determine the effect of Nd3+ ion concentration on the elastic properties of zinc-tellurite glass for the development of waveguide lasers. A series of Neodymium doped zinc-tellurite (NZT) glass system of composition [(TeO2) 0.70 (ZnO) 0.30] (1-x) Nd2O3 (x), x =0, 0.01, 0.02, 0.03, 0.04 and 0.05, were synthesized by using conventional melt-quenching method. XRD analysis confirmed the amorphous nature of the glass; the FTIR confirmed the presence of TeO3 and TeO4 in the glass network. The density of the glass system increases with increase in neodymium concentration. The longitudinal ultrasonic velocity decreases from 3737.01 to 3045.23 ± 10 ms−1, and the shear velocity decreases from 1959.31 to 1887.81 ± 10 ms−1. The experimental results have shown that the elastic properties depend on the composition of the glass systems and the effect of neodymium (Nd2O3) within the glass network.